2022
DOI: 10.1007/s12471-022-01670-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram-based mortality prediction in patients with COVID-19 using machine learning

Abstract: Background and purpose The electrocardiogram (ECG) is frequently obtained in the work-up of COVID-19 patients. So far, no study has evaluated whether ECG-based machine learning models have added value to predict in-hospital mortality specifically in COVID-19 patients. Methods Using data from the CAPACITY-COVID registry, we studied 882 patients admitted with COVID-19 across seven hospitals in the Netherlands. Raw format 12-lead ECGs recorded within 72 h of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Although ECG data were derived from a single vendor, previous studies have shown that ECG-based deep learning results generalize well to other cohorts with different ECG manufacturers. 34 , 35 Despite QRS AREA being calculated manually, performance is identical to that of automated calculation. 36 Although measurement of LVESV is user dependent, excellent intra- and inter-observer reliabilities were previously demonstrated in a subpopulation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although ECG data were derived from a single vendor, previous studies have shown that ECG-based deep learning results generalize well to other cohorts with different ECG manufacturers. 34 , 35 Despite QRS AREA being calculated manually, performance is identical to that of automated calculation. 36 Although measurement of LVESV is user dependent, excellent intra- and inter-observer reliabilities were previously demonstrated in a subpopulation of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, even the most experienced clinicians may be unable to adjust and respond in a timely manner to the new situation. Thus, ML and AI models were proposed for clinical decision-making, helping detect complex patterns in large datasets [20,92,171,172]. Several studies have shown the capability of ML-based models to predict mortality at the level of individual patients [108,115,119,121], and the aggregate level of cities [119].…”
Section: Mortality Predictionmentioning
confidence: 99%